Successful Use of Intravitreal Bevacizumab and Pascal Laser Photocoagulation in the Management of Adult Coats’ Disease - Raoof, Naz (Medknow Publications & Media Pvt Ltd, 2013)
Traditional methods of managing exudative retinal detachment secondary to Coats’ disease have been associated with varying degrees of success. We describe a case of a 34 year-old male who presented with a sub-total exudative retinal detachment of the right eye that encroached upon the macula, associated with a vasoproliferative tumor secondary to Coats’ disease. The patient under-went successful treatment with two intravitreal injections of bevacizumab (Avastin, Genetech Inc., San Francisco, CA, USA) combined with targeted laser photocoagulation with a 532 nm Pascal laser (Topcon Corp., Tokyo, Japan). The visual acuity improved 5 days after the second intravitreal injection from 6/18 to 6/5, with no residual macular edema and complete regression of the vasoproliferative tumor. The improvement in visual acuity was maintained at 12 months post-treatment. We believe this is the first case report describing the successful use of Pascal laser photocoagulation with intravitreal bevacizumab in the treatment of Coats’ disease. Our aim was to defer laser treatment until ‘near total’ retinal reattachment and regression of the vasoproliferative tumor was achieved. There are, however, reports of vitreous fibrosis in patients with Coats’ disease treated with intravitreal bevacizumab. This suggests further long-term follow-up studies are required in patients treated with this approach.